2015
DOI: 10.1515/cmble-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain affects some microRNA profiles in pre-oeteoblasts.

Abstract: MicroRNAs (miRNAs) are important regulators of cell proliferation, differentiation and function. Mechanical strain is an essential factor for osteoblast proliferation and differentiation. A previous study revealed that a physiological mechanical tensile strain of 2500 microstrain (με) at 0.5 Hz applied once a day for 1 h over 3 consecutive days promoted osteoblast differentiation. However, the mechanoresponsive miRNAs of these osteoblasts were not identified. In this study, we applied the same mechanical tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Other analysis likewise estimated about 20% of genes is subjected to the potential control of miRNAs (Lewis et al, ). On account of the high‐throughput and easy operating, miRNA microarray technique has recently become a popular means to detect the miRNAs expression in various samples and its accuracy has been verified by multiple investigations (Chang et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other analysis likewise estimated about 20% of genes is subjected to the potential control of miRNAs (Lewis et al, ). On account of the high‐throughput and easy operating, miRNA microarray technique has recently become a popular means to detect the miRNAs expression in various samples and its accuracy has been verified by multiple investigations (Chang et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some miRNAs have been shown to induce enhancing or weakening of osteoblast function under different mechanical stimulations. miR-3077-5p, -3090-5p, -3103-5p, -466i-3p, and -466h-3p, which correlate with the key genes of osteoblast differentiation as revealed by bioinformatics analysis, were dramatically different under cyclic mechanical strain in MC3T3-E1 cells 13 , 14 . In addition, some miRNAs are involved in the process by which fluid shear stress induces MC3T3-E1 cell differentiation, such as miR-20a, miR-21, miR-19b, miR-34a, miR-34c, miR-140, and miR-200b 15 , 16 .…”
Section: Introductionmentioning
confidence: 92%
“…Microarray and bioinformatics analysis are effective and prompt methods to search for mechanosensitive miRNAs altering with different mechanical stimuli in osteogenic cells ( Table 1 ). Two microarray data of MC3T3-E1 cells subjected to a four-point bending stretch suggested that miR-3077-5p, -3090-5p, -3103-5p, -191*, and -3070a were significantly up-regulated, in contrast, miR-466i-3p, -466h-3p, -218 and -33 were down-regulated; accompanied by alkaline phosphatase (ALP) activity, mRNA levels of Alp , Ocn (osteocalcin), Col I (Collage I), and the protein levels of BMP-2 and BMP-4 increased in the mechanical stretch group [ 41 , 42 ]. Furthermore, analysis of putative target genes indicated that this mechanosensitive miRNAs might be involved in osteoblast differentiation [ 41 , 42 ].…”
Section: Mechanosensitive Mirnas and Osteogenic Differentiationmentioning
confidence: 99%